A new Western North Atlantic Ocean kitefin shark (Squaliformes: Dalatiidae) from the Gulf of Mexico - Grace, Mark A.; Doosey, Michael H.; Denton, John S. S.; Naylor, Gavin J. P.; Bart, Henry L. Jr.; Maisey, John G. (Zootaxa, 2019)
A new species of kitefin shark (Squaliformes; Dalatiidae) is described from the Gulf of Mexico (Western North Atlantic Ocean) based on five diagnostic features not seen on the only other known Mollisquama specimen, the holotype of Mollisquama parini Dolganov which was captured in the Eastern South Pacific Ocean. The new species, Mollisquama mississippiensis sp. nov., is distinguished from its congener by a putative pit organ located ventrally just posterior of the lower jaw margin center, photophores irregularly distributed along many areas of the body, 16 distinct ventral-abdominal photophore aggregations, and two differences associated with the dentition. Other potential distinguishing features are 10 fewer vertebrae than Mollisquama parini and six morphometric proportional differences that exceeded +/- 20% from the holotype.